The Platelet Count in Carcinoma of the Lung and Colon - Costantini, Vincenzo; Zacharski, Leo R; Moritz, Thomas E; Edwards, Richard L (Thrombosis and Haemostasis, 1990)
Platelet counts were evaluated in 714 patients with advanced non-small cell lung cancer (N-SCLC), small cell carcinoma of the lung (SCCL), and colon cancer entered to a clinical trial. Patients had not received prior chemotherapy. Platelet counts were not different in patients who had received radiation therapy prior to entry to the study. In comparison to the other tumor types, patients with N-SCLC demonstrated an increased prevalence of thrombocytosis (counts greater than 400,000/mm3), higher platelet counts at the time of entry to the study, higher over all mean platelet counts, relative preservation of high platelet levels during disease progression, and no relationship between platelet numbers and the amount of chemotherapy given. By contrast, platelet counts in patients with SCCL were negatively correlated with the absolute amount of cyclophosphamide and adriamycin given, and declined most dramatically with disease progression and death. Platelet numbers did not correlate with fibrinopep-tide A or fibrin split product levels suggesting that disseminated intravascular coagulation or fibrinolysis may have had less influence on platelet numbers than certain other factors. By contrast, significant correlations were found for all three tumor types between platelet numbers and other indicators of bone marrow function including anemia, total leukocyte count, and absolute neutrophil count; and the fibrinogen level. Based upon these findings, we postulate that the host response to malignancy, possibly in the form of production of bone marrow-stimulating cytokines, may play a prominent role in regulation of platelet counts in these (and perhaps other) neoplasms, and that a particularly prominent and persistent degree of marrow stimulation exists in patients with N-SCLC.